Strategi Komunikasi Interpersonal Guru Tunanetra dalam Pembelajaran Al-Qur’an dengan Murid di Madrasah Diniyah Takmiliyah Awwaliyah Ahlul Ihya’ Ponorogo - Fitri Annas Sholikhah; Andhita Risko Faristiana (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Learning the Koran requires special attention because of the high level of difficulty of the material. Blind teachers face complex challenges in classroom management and delivery of material, requiring special interpersonal communication strategies. This research aims to describe the interpersonal communication strategies of blind teachers in learning the Koran at MDTA Ahlul Ihya' Ponorogo, along with obstacles and solutions. A qualitative phenomenological approach was used by collecting data through observation, interviews and documentation from blind teachers, fellow teachers, students and parents. Data analysis includes reduction, presentation and drawing conclusions. The results show that communication strategies involve getting to know students personally, determining appropriate messages, methods and media. Barriers include difficulties in visual instructions, unclear use of symbols, impaired facilities, as well as semantic barriers due to incompatibility of language and background experience. The proposed solution includes deliberation and evaluation, collaboration with fellow teachers, meetings with student parents, and the creation of a learning guidebook.